Binge eating disorder and morbid obesity are associated with lowered mu-opioid receptor availability in the brain. (30th June 2018) - Joutsa, Juho; Karlsson, Henry K.; Majuri, Joonas; Nuutila, Pirjo; Helin, Semi; Kaasinen, Valtteri; Nummenmaa, Lauri
Highlights: The neurobiology of eating disorders is largely unknown. BED and morbid obesity are behaviorally different eating disorders. This study investigated brain mu-opioid function using 11C-carfentanil PET. Both conditions are associated with lowered brain mu-opioid receptor availability. Abnormal brain mu-opioid function may be common for all eating disorders. Abstract: Both morbid obesity and binge eating disorder (BED) have previously been linked with aberrant brain opioid function. Behaviorally these two conditions are however different suggesting also differences in neurotransmitter function. Here we directly compared mu-opioid receptor (MOR) availability between morbidly obese and BED subjects. Seven BED and nineteen morbidly obese (non-BED) patients, and thirty matched control subjects underwent positron emission tomography (PET) with MOR-specific ligand [ 11 C]carfentanil. Both subjects with morbid obesity and BED had widespread reduction in [ 11 C]carfentanil binding compared to control subjects. However, there was no significant difference in brain MOR binding between subjects with morbid obesity and BED. Thus, our results indicate that there is common brain opioid abnormality in behaviorally different eating disorders involving obesity.